2021
DOI: 10.1177/09673911211005341
|View full text |Cite
|
Sign up to set email alerts
|

An insight into thermal stability and decomposition kinetics of polybenzoxazine plasma treated graphene nanocomposites

Abstract: This research was targeted to investigate the effect of oxygen plasma treated graphene nanosheets (tGNSs) on the thermal stability of benzoxazine resin and to have a further and deeper mechanistic understanding of thermal decomposition kinetics of such nanocomposites in 0.5, 1 and 3 wt% of tGNS. The samples were prepared as reported in our previous study. The quality of dispersion of tGNSs within benzoxazine was investigated by X-Ray diffraction (XRD) and scanning electron microscopy (SEM) technique. Also, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The effect of plasma treatment on thermal properties observed due to incorporation of oxygenated species on to the filler surface. Moreover, due to this newly formed functionalities, strong interfacial adhesion may happened resulted enhanced thermal stability 109 . Overall, noticeable changes obtained in thermal stability of PT samples may due to barrier impact of h‐BN.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The effect of plasma treatment on thermal properties observed due to incorporation of oxygenated species on to the filler surface. Moreover, due to this newly formed functionalities, strong interfacial adhesion may happened resulted enhanced thermal stability 109 . Overall, noticeable changes obtained in thermal stability of PT samples may due to barrier impact of h‐BN.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, due to this newly formed functionalities, strong interfacial adhesion may happened resulted enhanced thermal stability. 109 Overall, noticeable changes obtained in thermal stability of PT samples may due to barrier impact of h-BN. Hence, modified nano blends with PT h-BN demonstrated high thermal stability than reported value 110 highly recommended for ESD applications.…”
Section: Thermal Stability Of Pvdf/psf/ H-bn Nano Blendsmentioning
confidence: 95%
“…70,71 Furthermore, the prepared nanocomposites exhibit a high ability to absorb thermal energy (higher heat capacity), which is responsible for the matrix’s first thermal degradation temperatures shifting to much higher temperatures. 72,73 On the other hand, the enhancement in the char yields of the developed nanocomposites is due to the absence of EG degradation at 800°C, as shown in Figure 8(f).
Figure 8.TGA curves of polybenzoxazine/EG nanocomposites.
…”
Section: Resultsmentioning
confidence: 93%
“…They came to the conclusion that the rate‐controlling process during the final decomposition stage of pure PBZ, with adequate char formation, or for all phases of densely filled nano‐SiO 2 PBZ composites, is diffusion. Furthermore, Karblaei‐Bagher et al 24 examined how oxygen plasma treated graphene nano‐sheets (tGNS) affected the thermal stability of benzoxazine resin. The results demonstrated that the incorporation of 1 wt% tGNS increased PBZ char formation by approximately 7 wt%.…”
Section: Introductionmentioning
confidence: 99%